Fenomeno De Resonancia De La Vibracion Inducida Por Desprendimiento De Vortices Del Viento Sobre Una Estructura Cilindrica Por El Modelo Armonico - Maqui Santos, José Fernando (2017)
The main objective of the present work was to analyze the behavior of the resonance phenomenon of the vibrations generated by relatively small forces due to the alternating vortex detachments that are formed when an air flow impinges on a cylindrical structure through the harmonic modeling. In order to develop the formulations of the behavior of the movement of the harmonic forces generated from the vortex detachments, the fundamentals were based on the empirical-analytical method, explaining how these vortexes are formed and then disengaged in an alternating and orderly manner. Using the database of the Laredo Meteorological Station obtained from the SENAMHI web page, it was possible to obtain estimates about the parameters involved in vortex detachments, obtained through computer simulation using SolidWorks Software and with help also the Excel Software to obtain the respective graphs of the studies to be carried out. In this project it was possible to develop a series of previous studies with the intention of obtaining the parameters with which the study corresponding to the phenomenon of resonance could be developed. With the equations of the movement of the vibrations deduced from the harmonic model, the study could be developed with the intention of analyzing the phenomenon of resonance, where from cylindrical pipes it was possible to obtain results that can be beneficial and considered when installing or build cylindrical structures in the open.